Perancangan Sistem Informasi Penjualan Pada Buckscorner Berbasis Web - Dewi, Putu Jessita Aryati; Dewi, Ni Kadek Intan Pramesti Kencana; Agustino, Dedy Panji (Universitas Multi Data Palembang, 2024)
Buckscorner faces challenges in managing inefficient sales data and limited market reach because it still relies on a manual sales process that requires customers to come directly to the store. To overcome these problems, this research aims to design a web-based Sales Information System that can automate the sales process, expand customer accessibility, speed up service, and improve sales data accuracy. The system design is equipped with excellent features such as flexible delivery options, including in-store pickup, as well as real-time order tracking. In addition, the system is also designed with an intuitive and responsive user interface, ensuring a seamless shopping experience for customers. This research uses the waterfall method in system design, integrating Data Flow Diagram to describe the data flow and work process of the system, and Entity Relationship Diagram to design an organized database. The result of this research is a web-based Sales Information System design that is expected to optimize Buckscorner's sales process, improve operational efficiency, expand market reach, and provide accurate sales data to support business decision making. With comprehensive features and a focus on user experience, the design of the web-based Sales Information System.